Classification of Omicron BA.1, BA.1.1, and BA.2 sublineages by TaqMan assay consistent with whole genome analysis data. (September 2022) - Hirotsu, Yosuke; Maejima, Makoto; Shibusawa, Masahiro; Natori, Yume; Nagakubo, Yuki; Hosaka, Kazuhiro; Sueki, Hitomi; Mochizuki, Hitoshi; Tsutsui, Toshiharu; Kakizaki, Yumiko; Miyashita, Yoshihiro; Omata, Masao
Highlights: TaqMan assay targeting spike Δ69-70, G339D, and Q493R distinguishes Omicron variants Omicron sublineage results from of whole genome sequencing and TaqMan assay were highly consistent In samples mutated with the TaqMan probe, the results need to be visually confirmed Abstract: Objectives: Recently, the Omicron strain of SARS-CoV-2 has spread and replaced the previously dominant Delta strain. Several Omicron sublineages (BA.1, BA.1.1, and BA.2) have been identified, with in vitro and preclinical reports showing that the pathogenicity and therapeutic efficacy differs between BA.1 and BA.2. We sought to develop a TaqMan assay to identify these subvariants. Methods: A TaqMan assay was constructed for rapid identification and genotyping of Omicron sublineages with 171 samples. We analyzed three characteristic mutations of the spike gene, Δ69–70, G339D, and Q493R, by TaqMan assay. The accuracy of the TaqMan assay was examined by comparing its results with the results of whole genome sequencing (WGS) analysis. Results: A total of 171 SARS-CoV-2 positive samples were analyzed by WGS and TaqMan assay. The 127 samples determined as BA.1/BA.1.1 by WGS were all positive for Δ69–70, G339D and Q493R by TaqMan assay. A total of 42 samples, determined as BA.2 by WGS, were negative for Δ69–70 but positive for G339D and Q493R by TaqMan. Two samples with G339N were determined to be inconclusive by the TaqMan method. Except for these two samples, the concordance rate between WGS and the TaqMan assay was 100% (169/169). Conclusion: TaqMan assays targeting characteristic mutations are useful for identification and discrimination of Omicron sublineages.